ANTIVIRAL ACTIVITY OF DIANTHUS SUPERBUSN L. AGAINST HEPATITIS B VIRUS IN VITRO AND IN VIVO - Li, Wei Guo; Wang, He-Qun (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Hepatitis is a viral infection of hepatitis B virus (HBV). Limitations of drug used in the management of it opens the interest related to alternative medicine. The given study deals with the antiviral activity of Dianthus superbusn L. (DSL) against HBV in vitro & in vivo. Material and Methods: In vitro study liver cell line HepG2.2.15 was used by transinfected it with HBV. Cytotoxicity stduy was performed by using different concentrations of DSL such as 50, 100, 200, 500 & 1000 μg/ml. Anti HBV activity of DSL was estimated by assesing the concentration of HBsAg and HbeAg in cell culture medium by using ELISA. Whereas in vivo study was performed on ducklings and antiviral activity of DSL (100, 200, 400 mg/kg) was confirmed by estimating the serum concentration of HBV DNA and histopathology study of hepatocytes in HBV infected ducklings. Result: Result of the study suggested that >500 μg/ml concentration of hydroalcoholic extract of DSL was found tobe cytotoxic. It was also observed that DSL significantly (p<0.05) reduces the concentration of antigenes in cell culture media as per the concentration and days of treatment dependent. Moreover in vivo study confirms the anti viral activity of DSL (200 & 400 mg/kg) as it significantly (p<0.05) decreases the serum concenetration of HBV DNA in HBV infected dukling compared to control group. Histopathology study was also reveals the hepatprotective effect of DSL in HBV infected ducklings. Conclusion: The given study concludes the antiviral activity DSL against HBV by in vitro and in vivo models.